2020
DOI: 10.30659/e.5.2.214-224
|View full text |Cite
|
Sign up to set email alerts
|

Students� English business communication self-efficacy and their career aspirations

Abstract: Self-efficacy, which is defined as people�s judgment on their ability to carry out tasks and exercise control over events, is believed to be determinant in the success of learning and career aspiration.� The study was conducted to measure students� self-efficacy in making English business communication, their career aspiration, and the relationship between them. Sixty one students served as the respondents for the study.� Data were collected by using Likert-typed questionnaires after students attended an ESP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Students perceived self-efficacy influences professional aspirations [12], and self-efficacy contributes to people's career decision-making [13]. Other studies [14]- [16], all confirmed that there is a correlation between self-efficacy and career choice and aspiration. However, studies focusing on English-speaking efficacy are still very limited.…”
Section: Introductionmentioning
confidence: 93%
“…Students perceived self-efficacy influences professional aspirations [12], and self-efficacy contributes to people's career decision-making [13]. Other studies [14]- [16], all confirmed that there is a correlation between self-efficacy and career choice and aspiration. However, studies focusing on English-speaking efficacy are still very limited.…”
Section: Introductionmentioning
confidence: 93%
“…Bandura (1997) mengatakan bahwa Self-efficacy menentukan proses pengambilan keputusan karir (aspirasi karir) seseorang. Hasil penelitian sebelumnya menunjukkan bahwa Selfefficacy berpengaruh terhadap aspirasi karir (Hartono & Sari, 2020;VK & Padmanabhan, 2016) dan mampu meningkatkan kemandirian dalam pengambilan keputusan karir (Reddan, 2015). Aspirasi karir dapat diartikan sebagai sekumpulan kebutuhan, motif, dan niat perilaku yang diartikulasikan oleh individu sehubungan dengan pilihan bidang karir yang berbeda (VK & Padmanabhan, 2016).…”
Section: Pendahuluanunclassified
“…Hasil penelitian ini sesuai dengan penelitian sebelumnya yang menunjukkan bahwa Selfefficacy berpengaruh terhadap aspirasi karir (Gushue et al, 2006;Hartono & Sari, 2020;Reddan, 2015;Sawitri, 2009;VK & Padmanabhan, 2016). Menurut Subaidi (2016) Self-efficacy memengaruhi seseorang dalam berpikir, merasa, memotivasi diri, dan bertindak.…”
Section: Pembahasan Pengaruh Self-efficacy Terhadap Aspirasi Karir Bi...unclassified